CHANGES IN PLASMA LEVELS OF STEROID HORMONES DURING SEXUAL MATURATION OF MALE HELICOPTER CATFISH (WALLAGO ATTU) IN CAPTIVITY - Duc Nghia Vo; Thi Thu An Le; Ngoc Phi Chau; Van Huy Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
In order to provide reliable indicators of the spawning season of captive helicopter catfish (Wallago attu), this study evaluated the temporal variation in gonadosomatic index (GSI), plasma levels of testosterone (T), and 11-ketotestosterone (11-KT) in male broodstock in captivity. GSI was estimated as the percentage of the relative weight of testis to total body weight. Plasma levels of sex steroids were determined by enzyme-linked immunosorbent assay (EIA). Testis samples were dehydrated and embedded in paraffin, then sectioned at 5 μm thickness. The highest level of T (402.1 ± 16.7 pg/mL) was found in June, followed by a peak in 11-KT level (76.9 ± 4.7 pg/mL) in May. Testes containing the highest concentrations of spermatozoa were observed from June to August. The GSI of males increased significantly from January to June and peaked in July (2.14%). Taken together, we conclude that the spawning season of captive helicopter catfish occurs from June to August. These results will contribute to the basic knowledge of the reproductive biology of helicopter catfish, which can be useful in artificial breeding.